2022
DOI: 10.1088/1361-6560/ac43fc
|View full text |Cite
|
Sign up to set email alerts
|

PET respiratory motion correction: quo vadis?

Abstract: Positron emission tomography (PET) respiratory motion correction has been a subject of great interest for the last twenty years, prompted mainly by the development of multimodality imaging devices such as PET/computed tomography (CT) and PET/magnetic resonance imaging (MRI). PET respiratory motion correction involves a number of steps including acquisition synchronization, motion estimation and finally motion correction. The synchronization steps include the use of different external device systems or data dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 218 publications
0
15
0
Order By: Relevance
“…Our results showed that MCIR reduced motion artifacts on tumors in the regions vulnerable to respiratory motions. Respiratory motion is one of the major factors causing motion artifacts in PET/CT (7,(19)(20)(21). In this study, the observers identified lesion motions in 52.4-56.3% of patients, suggesting respiratory motion correction may potentially bring benefits to many patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that MCIR reduced motion artifacts on tumors in the regions vulnerable to respiratory motions. Respiratory motion is one of the major factors causing motion artifacts in PET/CT (7,(19)(20)(21). In this study, the observers identified lesion motions in 52.4-56.3% of patients, suggesting respiratory motion correction may potentially bring benefits to many patients.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of respiratory motion correction for PET imaging has prompted a series of technical developments (7). Gated image reconstruction is a basic approach for respiratory motion correction in which PET data are allocated into several gates according to their phase or amplitude in the respiratory waveform.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, motion estimation has been a subject of significant research interest in a range of imaging modalities [8,9,10,11,12]. Several computational techniques for acquisitions and correction of motion and motion-corrected image reconstruction have been developed in parallel to the advancement of hardware [13,14,15,16,17,18,19]. Image-based motion synchronization and detection has been studied in [20,21,22], where filtering is used to separate respiratory and cardiac signals in PET. In this paper we consider examples in dynamic MRI, where both deliberate imaging dynamics such as morphological motion or contrast inflow as well as undesired dynamics such as breathing motion play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, image reconstruction for MRI with motion correction has been studied in detail, see [14,23,24] and the references therein. Most motion compensation strategies have not found widespread acceptance in clinical practice, mainly due to the complexity of their implementation and the associated cost or computational burden [13,14]. In this work we develop a method based on generator neural networks that exhibits very successful results in motion separation for cardiac MRI images with respiratory motion.…”
Section: Introductionmentioning
confidence: 99%